Cover Image, Volume 11, Issue 3. (May 2017) - Zhao, Xuebing; Li, Siming; Wu, Ruchun; Liu, Dehua
Abstract : The cover image, by Xuebing Zhao et al., is based on the Review Organosolv fractionating pre‐treatment of lignocellulosic biomass for efficient enzymatic saccharification: chemistry, kinetics, and substrate structures, DOI:10.1002/bbb.1768 . Abstract : The cover image, by Xuebing Zhao et al., is based on the Review Organosolv fractionating pre‐treatment of lignocellulosic biomass for efficient enzymatic saccharification: chemistry, kinetics, and substrate structures, DOI:10.1002/bbb.1768 .